My Grandma is Great - Goldsack, Gaby, 1966-; Walker, Sara (Illustrator) (Bath, England : Paragon, 2003)
A young boy describes his grandmothers good qualities.
Keywords: Grandmothers -- Juvenile fiction; Grandchildren -- Juvenile fiction; Grandparent and child -- Juvenile fiction; Picture books